JENIS-JENIS MAKROALGA EPIFIT PADA BUDIDAYA (Kappaphycus alvarezii) DI PERAIRAN TELUK GERUPUK LOMBOK TENGAH - Mursal Ghazali; Mardiana Mardiana; Menip Menip; Bangun Bangun (Universitas Mataram, 2018)
Abstract:Epiphytes are organisms that attach to other organisms to support their growth and development. One type of epiphytes that has a negative impact on the host is algae (macroalgae). This algae is a competing organism for cultivation algae (Kappaphycus alvarezii). This research was conducted From May to October 2017 in Gerupuk Bay, Central Lombok. The aim of the research is to find out the types of macroalgae epiphytes on macroalgae kappaphycus alvarezii. This research was conducted using exploratory methods by taking seaweed samples overgrown with epiphytes, the research data obtained were descriptive analisys. As supporting data, environmental parameters are measured including temperature, pH, salinity, DO, phosphate, and NH4. Based on the results of exploration found 13 species of epiphytic algae in kappaphycus alvarezi cultivation, namely: Chaetomorpha linum, Chaetomorpha linum, Cladophora dalmatica, Acanthophora spicifer, Batrachospermum sp, Callithamnion sp., Caulachantus ustulatus, Ceramium sp, Hypnea spinnosa, Hypnea spinella, Hypnea sp, Polysiphonia brodiaei , Spyridia filamentosa. The type of epiphytes found that grows in both cultivation methods and some others are found only in one method. Meanwhile, data on environmental parameters are in the optimal range for macroalgae growth.This data is expected to be used as a consideration for the cultivateddevelopment in the Gerupuk Bay cultivation center.ÃÂ Keywords : Macroalgae, Epiphytes, Aquaculture,ÃÂ Kappaphycus alvarezii